FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI DAN PENDAPATAN USAHATANI CENGKEH (Studi Kasus di Kecamatan Ogodeide Kabupaten Tolitoli) - Fatmah Fatmah; Made Antara; Saiful Darman (Agroland: Jurnal Ilmu-ilmu Pertanian, 2015)
This research aimed to determinefactors influencing the production of clove farmingsand their income at Ogodeide district ofTolitoli regency. This research was conducted from August to October 2015. Data wasobtainedfrom 84 clove farmers who were selected using a simple random technique. The data was processed and analyzed by using production function of Cobb-Douglass. The results showed that simultaneously, the independent variables (X) significantly influence the dependent variable (Y) and the coefficient of determination (R2) was 0.90. Based on the partial test, it is obvious that there are four variables significantly influence the cloves production including the number of productive trees (X1), the use of ZA fertilizers (X3), the use of ponska fertilizer(X4), and the labors (X5) while the age of cloves variable (X2) has no significant influence to the clove production at Ogodeide district of Tolitoli regency. The income analysis suggests that the income generated by the farmer was IDR58,102,598.98/year, in average. Keywords: Clove farming, income, production factors.